2020
DOI: 10.1001/jamaoto.2020.2497
|View full text |Cite
|
Sign up to set email alerts
|

Association of Poorer Hearing With Longitudinal Change in Cerebral White Matter Microstructure

Abstract: IMPORTANCE There is a dearth of studies that examine the association between poorer hearing and change in cerebral white matter (WM) microstructure.OBJECTIVE To examine the association of poorer hearing with baseline and change in WM microstructure among older adults. DESIGN, SETTING, AND PARTICIPANTSThis was a prospective cohort study that evaluated speech-in-noise, pure-tone audiometry, and WM microstructure, as measured by mean diffusivity (MD) and fractional anisotropy (FA), both of which were evaluated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…There is growing evidence of a link between structural brain findings and hearing loss with aging ( Lin et al, 2014 ; Qian et al, 2017 ; Rigters et al, 2017 , 2018 ; Uchida et al, 2018 ; Armstrong et al, 2019 , 2020a , b ; Xu et al, 2019 ; Ha et al, 2020 ; Isler et al, 2021 ). Various studies have reported results using different assessments of brain structure and auditory function; the heterogeneity of study designs makes it difficult to discuss them in a unified manner ( Jafari et al, 2021 ).…”
Section: Brain Morphology and Age-related Hearing Lossmentioning
confidence: 99%
See 3 more Smart Citations
“…There is growing evidence of a link between structural brain findings and hearing loss with aging ( Lin et al, 2014 ; Qian et al, 2017 ; Rigters et al, 2017 , 2018 ; Uchida et al, 2018 ; Armstrong et al, 2019 , 2020a , b ; Xu et al, 2019 ; Ha et al, 2020 ; Isler et al, 2021 ). Various studies have reported results using different assessments of brain structure and auditory function; the heterogeneity of study designs makes it difficult to discuss them in a unified manner ( Jafari et al, 2021 ).…”
Section: Brain Morphology and Age-related Hearing Lossmentioning
confidence: 99%
“…From a longitudinal analysis of the BLSA, an association between hearing and changes in WM microstructure has also been published ( Armstrong et al, 2020b ). Three hundred and fifty-six cognitively normal adults (age range: 55–99, mean age: 73.5 ± 8.8 years) who had at least one hearing assessment and serial MRI session with DTI were evaluated with a mean follow-up time of 1.7 years.…”
Section: Brain Morphology and Age-related Hearing Lossmentioning
confidence: 99%
See 2 more Smart Citations
“…These subtle asymmetries in HL provide variability that allows laterality-based studies (19,20). Neuroimaging studies have demonstrated that HL is associated with lateralized changes in the right and left brain hemispheres (17,(21)(22)(23). Indeed, other studies have shown that left and right ears demonstrate asymmetric input to the ascending auditory pathways, which likely reflects the hemispheric asymmetry of the central nervous system and possibly its processing of different types of stimuli (e.g., speech vs. tones) (24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%